Measurements of SiH4/H2 VHF Plasma Parameters with Heated Langmuir Probe - Yamane, Tsukasa; Nakao, Sachiko; Takeuchi, Yoshiaki; Muta, Hiroshi; Ichiki, Ryuta; Uchino, Kiichiro; Kawai, Yoshinobu (International Conference on Plasma Surface Engineering, 2013)
The parameters of SiH4/H2 VHF plasma were measured as a function of silane gas concentration with a heated Langmuir probe. When the sailane gas concentration was increased, the nagative ion density increased. The negative ion density was estimated from the reduction of the electron saturation current. In addition, the dependence of the sheath potential on the silane gas concentration agreed with the theoretical values derived from the Bohm sheath equation including negative ions.